Notification that new names of prokaryotes, new combinations and new taxonomic opinions have appeared in volume 65, part 11, of the IJSEM - Oren, Aharon (Int J Syst Evol Microbiol, 2016)
This listing of names of prokaryotes published in a previous issue of the IJSEM is provided as a service to bacteriology to assist in the recognition of new names and new combinations. This procedure was proposed by the Judicial Commission [Minute 11(ii), Int J Syst Bacteriol 41 (1991), p. 185]. The names given herein are listed according to the Rules of priority (i.e. page number and order of valid publication of names in the original articles).